MassMin 2020: Proceedings of the Eighth International Conference &Amp; Exhibition on Mass Mining 2020
DOI: 10.36487/acg_repo/2063_35
|View full text |Cite
|
Sign up to set email alerts
|

Cave propagation factor for caving rate and drawpoint productivity forecasting at PTFI

Abstract: Monitoring of fracture limits, cave backs and drawpoint fragmentation at both the Grasberg Block Cave (GBC) and Deep Mill Level Zone (DMLZ) caves at PT Freeport Indonesia's operations suggest that Cave Propagation Factor (CPF), weak and persistent vein intensity and hydrofracture spacing exert a strong control on the caving rate and primary fragmentation within the cave back. CPF in this case is defined as the ratio of cave back stress to defected rock strength and can vary significantly across the cave back, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Bewick 2021; Jakubec 2013). Since its conception in 2019 (Pierce et al 2020), application of the FragPro methodology has indicated a need to factor vein intensities based on the ratio of vein to host point load index, Is50v:Is50h. This recognises that a weak vein will have a stronger impact on fragmentation when embedded in a rock mass of greater (rather than equivalent) strength.…”
Section: Primary Fragmentation Block Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Bewick 2021; Jakubec 2013). Since its conception in 2019 (Pierce et al 2020), application of the FragPro methodology has indicated a need to factor vein intensities based on the ratio of vein to host point load index, Is50v:Is50h. This recognises that a weak vein will have a stronger impact on fragmentation when embedded in a rock mass of greater (rather than equivalent) strength.…”
Section: Primary Fragmentation Block Modelmentioning
confidence: 99%
“…This paper begins with a summary of the fragmentation block model development, focusing on refinements/additions since Pierce et al (2020). This is followed by a description of the production forecasting workflow and the process for visualising and reconciling forecast outcomes against actual fragmentation (from drawpoint mapping) and hang-up frequencies.…”
Section: Introductionmentioning
confidence: 99%